2011
DOI: 10.1002/lapl.201110109
|View full text |Cite
|
Sign up to set email alerts
|

Fractional photon-assisted tunneling of ultra-cold atoms in periodically shaken double-well lattices

Abstract: Fractional photon-assisted tunneling is investigated both numerically and analytically in a double-well lattice. While integer photon-assisted tunneling is a single-particle effect, fractional photon-assisted tunneling is an interactioninduced many-body effect. Double-well lattices with few particles in each double well are ideal to study this effect far from the mean-field effects. It is predicted that the 1/4-resonance is observable in such systems. Fractional photon-assisted tunneling provides a physically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As the ansatz in Eqs. (9) and (10) is not unique, one can also derive effective equations for which J eff becomes complex [15,30,31]. Choosing, e.g., complex phasefactors such that the exponential in the ansatz is 1, i.e.,…”
Section: B Complex J Eff Induced Via Phase-jumpsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the ansatz in Eqs. (9) and (10) is not unique, one can also derive effective equations for which J eff becomes complex [15,30,31]. Choosing, e.g., complex phasefactors such that the exponential in the ansatz is 1, i.e.,…”
Section: B Complex J Eff Induced Via Phase-jumpsmentioning
confidence: 99%
“…The effective tunnelling can be both zero and negative. Note that sometimes the physics is described by a zero [5] whereas in other cases the dynamics is governed by the other Bessel functions [15]. Equations ( 14) and (15) yield the effective, time-independent Hamiltonian:…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a shortcoming of the current scheme is that SOC exists in only one spatial direction. This has become one of the bottlenecks for an experimental realization of topological matters in ultracold atoms.Both theoretical and experimental interest in shaken optical lattices have been increasing recently [14][15][16][17][18][19][20]. It has been shown that such a scheme allows one to manipulate both the magnitude and the sign of tunneling constants.…”
mentioning
confidence: 99%